Implementation of the Measure of Returning Children in Conflict With the Law to Their Parents by Investigators From the Perspective of the Juvenile Criminal Justice System : A Study at the North Aceh Resort Police Department - Cicit Aisyah; Rizanizarli Rizanizarli; Teuku Muttaqin Mansur (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
Law Number 11 of 2012 on the Juvenile Criminal Justice System mandates that the resolution of juvenile cases should prioritize a restorative justice approach through diversion in order to ensure child protection and restore social relationships. One form of diversion is the return of children in conflict with the law to their parents for guidance and supervision within the family environment. Data from the North Aceh Resort Police for the period 2024–2025 indicate that all cases involving Children in Conflict with the Law were resolved through restorative justice, with the subsequent measure being the return of the child to their parents. This study aims to analyze the conformity of returning children to their parents with the principles of restorative justice and child protection, examine the balance of legal protection between child offenders and victims, and assess the considerations employed by investigators in implementing diversion at the North Aceh Resort Police. This research employs an empirical legal method with a socio-juridical approach. Data were collected through interviews with investigators from the Women and Children Protection Unit (PPA) of the North Aceh Resort Police, assistant investigators, officers of the Correctional Center (Bapas), and parents or guardians of the children involved, supported by a literature review of statutory regulations, books, scholarly journals, and previous studies. The findings reveal that the return of children to their parents through diversion reflects the principles of restorative justice and child protection by prioritizing rehabilitation, restoration, and the best interests of the child. This practice also provides balanced legal protection for both child offenders and victims through the involvement of all parties in the reconciliation process and the restoration of victims’ rights. Furthermore, investigators consider legal, social, and psychological factors, including the fulfillment of diversion requirements, the existence of a settlement agreement, and the family’s capacity to guide and supervise the child. It is recommended that the North Aceh Resort Police strengthen coordination with the Correctional Center, the Regional Technical Implementation Unit for Women and Children Protection (UPTD PPA), social workers, and the child’s family in order to enhance supervision, ensure continuous guidance, and support victim recovery following the implementation of diversion.